2020
DOI: 10.1111/bju.15129
|View full text |Cite
|
Sign up to set email alerts
|

Not all prostate cancer is the same – patient perceptions: an Asia‐Pacific region study

Abstract: Objective To explore the perceptions of patients living with different stages of prostate cancer across the Asia‐Pacific (APAC) region, as while extensive quantitative research has been undertaken into outcomes of treatments for prostate cancer, little in the way of qualitative research has been performed looking at subjective perceptions of patients in regard to their perceived deficits in the treatment of this condition and such research is particularly lacking in reference to the APAC region. Patients and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Public awareness of prostate cancer and its disease progression plays a pivotal role in improving the outcome of patients with prostate cancer. Previous studies suggested that gaps in prostate cancer awareness and knowledge about PSA testing, disease prognosis as well as prostate cancer treatment may reflect different levels of education, socioeconomic status, healthcare provision and media coverage across various populations 15,16 . It has also been shown that the prostate cancer mortality‐to‐incidence ratio was significantly lower in countries with high GDP and healthcare expenditure than those of middle‐to‐low income countries 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Public awareness of prostate cancer and its disease progression plays a pivotal role in improving the outcome of patients with prostate cancer. Previous studies suggested that gaps in prostate cancer awareness and knowledge about PSA testing, disease prognosis as well as prostate cancer treatment may reflect different levels of education, socioeconomic status, healthcare provision and media coverage across various populations 15,16 . It has also been shown that the prostate cancer mortality‐to‐incidence ratio was significantly lower in countries with high GDP and healthcare expenditure than those of middle‐to‐low income countries 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…The PCOR‐ANZ registry data are significant for all clinicians managing men with prostate cancer in Australia and New Zealand, particularly as quality indicator reporting commences. Patients in the region trust healthcare providers to manage their prostate cancer, and this reporting mechanism is a key driver for registries achieving improvement in routine care [4,5]. Previous work via a Delphi process, has clarified 12 indicators for quality of care for prostate cancer, with further indicators relating to radiation oncology under development [6].…”
Section: Figmentioning
confidence: 99%
“…Investigation and treatment of prostate cancer (PCa) is highly topical, as it is the second most common cancer in men worldwide [1,2]. While there has been an overall decrease in treatment of PCa, attributable to active surveillance of low-risk PCa in younger age groups, in recent years, we have seen an increase in patients over the age of 65 years who are successfully treated for intermediate-and high-risk PCa by external beam radiotherapy or radical prostatectomy (RP) [3].…”
Section: Introductionmentioning
confidence: 99%